Pagbabalik sa tribo - Philippine Center for Investigative Journalism; The Probe Team. (Manila PCIJ and The Probe Team, 1999)
When Auraeus Solito discovers that he is a member of the Pala'wan tribe he return to his native land to begin a journey of self-discovery and the recovery of his tribe's history. This documentary also shows the problems that the tribe faces, including poverty, discrimination and the illegal grabbing of their ancestral domain.
Unang ipinalabas sa The Probe Team sa GMA-7 noong ika-18 ng Mayo 1999.
Keywords: Palawan (Philippine people); Minorities -- Philippines -- Palawan